Rational harnack curves on toric surfaces (2016)
"In this thesis we focus on rational Harnack curves as their importance was evident. Our main results provide explicit parametrimtions of rational Harnack curves on any toric surface. We hope that with further work these parametrimtions Will be useful to calculate the mochili space of Harnack curves with any given Newton polygon with applications to dimer theory."Página 5 de la introducción.